Effects of Various Biomolecules and Ultrasonic Wave on the Physic0 Chemical Properties of Zinc Oxide Synthesized by Hydrolysis Method - Shapiei, Ahmad Alfaiz (, whereas other ZnO-biosubtrates agglomeration did not show any changes to the typical ZnO phase being observed based on the PXRD spectra obtained. Thus layered ZnO can be regarded as an inorganic vector or host structure in directing the physicochemical transition of the layer ZnO-Lcystine in the agglomeration process whereby a lamellar solid is being formed. The phase transformation that consists of ZnO-L-cystine agglomerate was shown to have formed a significant chemical constituent with net Lcystine composition of 21 % and 37 % ex CHNS and EDX measurement compared to the maximum of 5 % and 2 % obtained from other ZnObiosubstrate agglomerations. The intercalated ZnO-L-cystine agglomeration has a higher BET surface area of around 53 m2/g with wider pore size distribution compared to between 4- 34 m*/g (with sharper pore size distribution pattern) of all other ZnObiosubstrate agglomeration. The phase transformation of ZnO-fructose agglomerate however has shown to have a structure directing role in forming well divided monospherical microcrystallines. Together with other ZnObiosubstrate agglomeration, it was observed that the degree of structural regularities based on it's surface morphology is in correlation to the Zn/O mole ratio obtained from EDX calculation whereby low Zn/O mole ratio was observed to display better crystallinity or higher order of ZnO-biosubstrate structural transformation. Nonetheless, the influence of fructose biomolecule on the structural transformation was demonstrated further in a molar concentration gradient study, whereby grain-like surface morphology had nucleated into well divided monospheres in the crystal growing process as observed by SEM images from 0.01 M to 0.20 M fructose used. The final agglomerate at the highest molar concentration used (that yields monospherical morphology) was found to show a marked increase in net fructose composition at about 16 % from 6 % at it's lowest based on the EDX result. On the contrary, PXRD and FTIR data regarding the physico-chemical strata of the ZnO phase in the ZnO-fructose agglomerate remains unchanged.Attemp to seek higher degree of structure-property feature of the ZnOfructose agglomeration, sonification method was done using the accelerated aging process to activate the electronic state of the solid solution containing layer ZnO and fructose biomolecule in a series of ultrasonic exposure time gradient at 0.20 M fructose where stable micro spherical nucleation was observed earlier. It was found that the influence of ultrasonic irradiation was able to further doubles the net composition of fructose present (i.e. to 35 %) in the ZnO-fructose agglomeration compared to conventional thermal aging method as mentioned earlier. It was noticed also that an equally good surface morphology without any deformities was produced only at longer sonification period i.e. at the 60th minutes. In more, the surface area has also shown to exhibit an increasing trend from 1 to 4.7 m2/g gaining higher pore volume or pore size distribution at longer sonification period due to higher chemical reactivity generated in the solid solution. The BET surface area however, was only half the surface area generated by the hydrothermally aged ZnO-fructose agglomeration of 9.4 m2/g. The PXRD and FI'IR data regarding the physico-chemical characteristic also shows that the ZnO phase in the ZnO-fructose agglomerate remains unchanged with the use of ultrasound. Although no significant structural transformation or changes in the lattice orientation of the layer ZnO in the solid solution during ZnO-fructose agglomeration in the conventional or the accelerated synthesis method described, the effect of fructose on the structure directing role and interdiffusion capability into the ZnO network is prevalent. It is also important to note that the increase in the porosity or pore profile of the ZnO-fructose aggregate due to the ultrasound is an additional aspect to enhance the structure-property relationship which was observed in this work., 2005)
In this study, the effect of different biosubstrates on the physicochemical properties of zinc oxide synthesized by the inorganic-organic agglomeration was characterized. The resulting materials containing layered ZnO was synthesized via hydrolysis mechanism between zinc nitrate precursor and the precipitator, sodium hydroxide at pH 10 in the presence of 0.10 M biosubstrates stabilized using the conventional thennal aging method. It was found that a pillared layered structure was formed when L-cystine biomolecule acting as a molecular propped, causing basal expansion of 10.1